Nitrogen Use Efficiency in Durum Wheat Under Different Nitrogen and Water Regimes in the Mediterranean Basin - Lupini, Antonio; Preiti, Giovanni; Badagliacca, Giuseppe; Abenavoli, Maria Rosa; Sunseri, Francesco; Monti, Michele; Bacchi, Monica (Frontiers in Plant Science, 2021)
Improving the nitrogen use efficiency (NUE) represents one of the main goals to reduce N input maximizing crop yield for sustainable agriculture. A NUE key strategy is the exploitation of genetic variation in available germplasm together with the understanding of molecular mechanisms governing this complex trait. Thus, NUE and its components, nitrogen uptake efficiency (NUpE) and nitrogen utilization efficiency (NUtE), and NUE-related traits heritability were evaluated in ancient (Cappelli, Capeiti, Russello and Mazzancoio) and modern (Messapia, Tiziana, Svevo and Normanno) wheat genotypes for tackling nitrogen (N) and/or water (W) limitation, in both growth chamber and field experiments. Our results exhibited a reduction of NUE, NUpE and NUtE under water and combined stress in all the genotypes, as expected. The contribution of genetic variability on phenotypic variation (heritability) was significant for NUtE, HI, PANU and biomass production traits. Moreover, the stress tolerance indexes, calculated and bi-plotted for both stresses, exhibited two distinct clusters for many traits then confirmed by principal component analysis (PCA). Although modern varieties showed higher crop yield and NUE under conventional N and W regimes, ancient varieties exhibited best performances to cope both stresses, mainly under W limitation. Finally, the usage index, which takes into account total biomass increase, underlined that ancient genotypes were less affected by both stress during crop cycle. In particular, these genotypes showed the best performances for NUE and its components under both stress at stem elongation (SE) and milk ripening (MR) as showed also by PANU and N transporter gene expressions. In conclusion, the identification of NUE traits during specific crop cycle stage, under both N and W limitation, will help the breeding of more resilient varieties in a Mediterranean sustainable agriculture by reducing N supply..